Small business management an entrepreneurial emphasis - Justin G. Longenecker (Thomson South-Western, 2006)
For more than three decades, Small Business Management has been the most widely used text in its field.The authors diverse academic backgrounds in management, marketing and finance have enabled them to provide well-balanced coverage of small business issues. The text continues to be praised for its balanced presentation of current theories and practice related to starting and managing small business firms.